A Comparison of Expectations of Physicians and Patients with Chronic Pain for Pain Clinic Visits. Issue 3 (15th March 2016) - Calpin, Pádraig; Imran, Ather; Harmon, Dominic
Abstract: Background: The patient–physician encounter forms the cornerstone of every health service. However, optimal medical outcomes are often confounded by inadequate patient–physician communication. Chronic pain is estimated to affect over 25% of the population. Its effects are multifaceted with patients at increased risk of experiencing emotional and functional disturbances. Therefore, it is crucial to address all components of the patient's pain experience, including beliefs and expectations. It is our understanding that no other study to date has evaluated the expectations of physicians and compared them to those of patients for pain clinic visits. We sought to describe and compare expectations of chronic pain patients and their physicians during a clinic consultation. Methods: We performed a retrospective review on patients attending the pain clinic for the first time who were enrolled and completed a questionnaire asking their expectations for their clinic visit as well as outcomes that would satisfy and disappoint them. Pain physicians were also included. We compared physicians' to patients' responses and evaluated relationships between patient responses and age, gender, pain location, Pain Self‐Efficacy, Pain Catastrophizing Scale, and the Hospital Anxiety and Depression Scale. Results: One hundred chronic pain patients and 10 pain physicians were surveyed. Patients' clinical expectations for visits focused primarily on some pain relief (34%), education on the cause of pain (24%), and a definitive diagnosis (18%). Physician's expectations included formulation and communication of a management plan (70%), patient assessment for cause of pain (50%), and the education of patients on the cause of pain (40%) as important aims. Pain relief would satisfy the majority of patients (74%) and physicians (70%). No improvement would cause greatest dissatisfaction for patients (52%), but causing more harm would be disappointing to physicians (50%). Gender, age, pain location, and sleep quality all significantly influenced patients' expectations and affective pain comorbidities. Conclusion: We found some agreement and some discordance of clinical expectations between pain patients and physicians. Patient factors may also impact on expectations and comorbidities. Findings from this study will help doctors consider patients' expectations in planning pain clinic visits, improve patient–doctor communication and pain management, and may lead to further hypothesis‐driven studies.